Financial disclosure policy in an entry game - Darrough, Masako N; Stoughton, Neal M (Journal of Accounting and Economics, 1990)
This paper analyzes incentives for voluntary disclosure of proprietory information. Proprietory information, if disclosed, provides strategic information to potential competitors, but can be helpful to the financial market in valuing the firm more accurately. Focusing on a stylized model of a static entry game, we show that a fully revealing disclosure equilibrium exists when the prior of the market is optimistic or the entry cost is relatively low. When the prior is pessimistic or the entry cost is high, however, both non- and partial-disclosure equilibria obtain. Our analysis predicts that competition in the product market encourages voluntary disclosure.